The Improvement of Nutrient Quality of Cassava Peel Waste Through Fermentation with Natura as Quail Feed - Ade Djulardi; Nuraini Nuraini; Reni Sumarni (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
This research aims to improve the quality of cassava peel waste through fermentation processing with Natura used as alternative feed which reduces the use of corn and concentrate in feed of laying quail in the grower period. This research consisted of two phases. Phase 1 improvement the quality of cassava peel waste using fermentation technology with Natura, organic decomposer containing multi enzyme, xylanase, beta-glucanase, pectinase, amylase, lipase, protease and phytase and also contain probiotics, Acetobater sp, Bacillus sp, Lactobacillus sp, Streptomyces sp, Aspergillus sp, Sacaromyces sp, and Trichoderma sp. Phase 2: the best fermented cassava peel waste experiment at phase 1 (using completely randomized factorial design consisted of 3x3 with 3 replications: 3 levels of Natura dose; 1, 2, and 3% and 3 levels of fermentation length; 7, 11, and 15 days) to the performance of laying quail in the grower period. The research methods at phase 2 used experimental method with completely randomized design (4 treatments and 5 replications): 0%, 4%, 8%, 12% and 16% of fermented cassava peel waste in the feed of laying quail in grower period (1-4 weeks). The best result in phase 1 was treatment with dose of 3% and 11 days of fermentation length with crude protein content: 14.14%, nitrogen retention: 62.90), crude fiber digestibility (47.58%) and crude fiber content (11.34%). The result of phase 2 was that the addition of fermented cassava peel waste 16% in the feed of laying quail in grower period gave a significantly higher effect on feed consumption, weight gain, and significantly had the lowest feed conversion compared to other treatments. Conclusion, that 3% Natura inoculum dose with 11 days of fermentation was the best treatment to increase the content and quality of cassava peel waste nutrient. The addition of fermented cassava waste with Natura up to 16% in feed could maintain the performance of laying quail in grower period, also reduced the use of corn 10% and concentrate 12% in feed.